Evolution of gypsy endogenous retrovirus in the Drosophila obscura species group. - Vazquez-Manrique, R.P.; Hernandez, M.; Martinez-Sebastian, M.J.; de Frutos, R. (Molecular Biology and Evolution, 2000)
The Ty3/gypsy family of retroelements is closely related to retroviruses, and some of their members have an open reading frame resembling the retroviral gene env. Sequences homologous to the gypsy element from Drosophila melanogaster are widely distributed among Drosophila species. In this work, we report a phylogenetic study based mainly on the analysis of the 5' region of the env gene from several species of the obscura group, and also from sequences already reported of D. melanogaster, Drosophila virilis, and Drosophila hydei. Our results indicate that the gypsy elements from species of the obscura group constitute a monophyletic group which has strongly diverged from the prototypic D. melanogaster gypsy element. Phylogenetic relationships between gypsy sequences from the obscura group are consistent with those of their hosts, indicating vertical transmission. However, D. hydei and D. virilis gypsy sequences are closely related to those of the affinis subgroup, which could be indicative of horizontal transmission.